The European bifurcation club Left Main Coronary Stent study: a randomized comparison of stepwise provisional vs. systematic dual stenting strategies (EBC MAIN). (18th May 2021) - Hildick-Smith, David; Egred, Mohaned; Banning, Adrian; Brunel, Philippe; Ferenc, Miroslaw; Hovasse, Thomas; Wlodarczak, Adrian; Pan, Manuel; Schmitz, Thomas; Silvestri, Marc; Erglis, Andreis; Kretov, Evgeny; et al.
Abstract: Background: Patients with non-left-main coronary bifurcation lesions are usually best treated with a stepwise provisional approach. However, patients with true left main stem bifurcation lesions have been shown in one dedicated randomized study to benefit from systematic dual stent implantation. Methods and results: Four hundred and sixty-seven patients with true left main stem bifurcation lesions requiring intervention were recruited to the EBC MAIN study in 11 European countries. Patients were aged 71 ± 10 years; 77% were male. Patients were randomly allocated to a stepwise layered provisional strategy ( n = 230) or a systematic dual stent approach ( n = 237). The primary endpoint (a composite of death, myocardial infarction, and target lesion revascularization at 12 months) occurred in 14.7% of the stepwise provisional group vs. 17.7% of the systematic dual stent group (hazard ratio 0.8, 95% confidence interval 0.5–1.3; P = 0.34). Secondary endpoints were death (3.0% vs. 4.2%, P = 0.48), myocardial infarction (10.0% vs. 10.1%, P = 0.91), target lesion revascularization (6.1% vs. 9.3%, P = 0.16), and stent thrombosis (1.7% vs. 1.3%, P = 0.90), respectively. Procedure time, X-ray dose and consumables favoured the stepwise provisional approach. Symptomatic improvement was excellent and equal in each group. Conclusions: Among patients with true bifurcation left main stem stenosis requiring intervention, fewer major adverse cardiac events occurred with a stepwise layered provisional approach than with planned dual stenting, although the difference was not statistically significant. The stepwise provisional strategy should remain the default for distal left main stem bifurcation intervention. Study registration: http://clinicaltrials.gov NCT02497014. Graphical Abstract: